Primary Renal Hydatid in Children - Jeff John; Bernard Marais (European Medical Journal Urology)
Isolated renal hydatid disease, caused by the larvae of the parasitic tapeworm Echinococcus granulosus is a rare phenomenon and accounts for only 2% of all reported cases. The authors report a case of a 12-year-old female who presented with right flank pain. Initial abdominal ultrasound revealed a complex cystic mass in the upper pole of the right kidney. A contrasted CT scan better defined it as a well-circumscribed cyst with multiple thin septations. Laboratory investigations showed eosinophilia and a positive IgG Echinococcus serology. Considering these radiological and laboratory findings, a tentative diagnosis of primary renal hydatid was made. With perioperative antihelmintic therapy, the authors used a combination of an open puncture-aspiration-injection-reaspiration technique pericystectomy to manage the isolated renal hydatid. Renal hydatid can easily be misinterpreted pre-operatively for more sinister renal cystic pathology, including cystic renal cell carcinoma. An accurate pre-operative diagnosis requires a high index of suspicion, especially in endemic regions. Surgical therapy, with perioperative antihelmintic therapy, offers the best chance of cure.